Crane overlap and operational flexibility: balancing utilization, duration, and safety. Issue 1 (2nd January 2018) - Al Hattab, Malak; Zankoul, Emile; Barakat, Mohammad; Hamzeh, Farook
Abstract : Purpose: With tower cranes being the site hubs, thoroughly planning and managing their operations can result in better construction performance. As urban spaces become more constricted, overlapping working radii of tower cranes becomes inevitable. While project planners are concerned with safety hazards, research has not comprehensively addressed workload distribution and synchronization of overlapping cranes. Therefore, this study aims at exploring the impact of overlapping cranes, used on high-rise buildings, on operational flexibility which is the balance between schedule duration, crane utilization and safety. Design/methodology/approach: A simulation model was developed and applied on a real project to analyze and compare the impacts of different overlap sizes. Seven scenarios of different overlap sizes, i.e. different number of tasks falling in the overlap space, were executed in the model; their results were plotted and analyzed. Findings: The outcomes result from several compounded factors such as the experience of planners and crane operators, the sequencing of critical versus non-critical activities and the overall effort and care taken when planning operations of overlapping cranes. Increasing overlap size can be beneficial or unfavorable depending on how properly planners allocate overlapping cranes to workload demand, keeping in mind that there are certain trade-offs while achieving operational flexibility. Originality/value: While project planners are concerned with safety hazards associated with crane overlaps, research has not been comprehensively nor proactively addressing the workload distribution and synchronization of overlapping crane processes. This study contributes to science by addressing the need to harness the flexibility in using overlapping tower cranes while minimizing the resulting interruptions and safety risks. This study sheds light on the potential benefits of allowing cranes to overlap while considering their collision free operations. Operational flexibility is seen as the balance between achieving shorter schedule durations and higher crane utilizations while maintaining collision free motion paths.